2012
DOI: 10.3109/0284186x.2012.728714
|View full text |Cite
|
Sign up to set email alerts
|

Ewing’s sarcoma family of tumors in Finland during 1990–2009: A population-based study

Abstract: Population-based studies including both bone and soft tissue ESFTs are few. In this nationwide, population-based study on Finnish bone and soft tissue ESFT patients, we find their treatment successful and results comparable to those previously published. Absence of metastases, young age at diagnosis and a peripheral primary tumor site were associated with a better prognosis. It seems that surgical resection of the primary tumor should be performed whenever adequate resection margins can be achieved. The role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…For Ewing sarcoma, the overall survival in both localized and metastatic disease has improved since 1990s, as indicated in other publications . More intensive chemotherapy (including high‐dose chemotherapy with stem cell support), advanced surgery and radiotherapy as well as surgery on lung metastases have all contributed to improved outcomes .…”
Section: Discussionmentioning
confidence: 84%
“…For Ewing sarcoma, the overall survival in both localized and metastatic disease has improved since 1990s, as indicated in other publications . More intensive chemotherapy (including high‐dose chemotherapy with stem cell support), advanced surgery and radiotherapy as well as surgery on lung metastases have all contributed to improved outcomes .…”
Section: Discussionmentioning
confidence: 84%
“…16 However, the latest population-based study showed that adding preoperative or postoperative radiation therapy to a surgical resection with at least a marginal margin did not improve outcome. 17 In our cases, 10 patients underwent local surgical resection including total hysterectomy with bilateral salpingo-oophorectomy with or without pelvic lymphadenectomy. Multiple chemotherapy regimens for treatment of PNETs have been reported, most of them based on trials of bone PNETs.…”
Section: Discussionmentioning
confidence: 99%
“…Current response rates of Ewing's sarcoma family of tumour (ESFT) patients to first-line chemotherapy are as high as 77% (Bacci et al , 2000; Yonemori et al , 2007; Gaspar et al , 2012; Serlo et al , 2012), demonstrating that some ESFTs are chemoresponsive. However, others are resistant to chemotherapy at diagnosis (23%), and this is known as intrinsic resistance.…”
mentioning
confidence: 99%